2015
DOI: 10.1523/jneurosci.3318-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

State-Dependent Population Coding in Primary Auditory Cortex

Abstract: Sensory function is mediated by interactions between external stimuli and intrinsic cortical dynamics that are evident in the modulation of evoked responses by cortical state. A number of recent studies across different modalities have demonstrated that the patterns of activity in neuronal populations can vary strongly between synchronized and desynchronized cortical states, i.e., in the presence or absence of intrinsically generated up and down states. Here we investigated the impact of cortical state on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
146
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(165 citation statements)
references
References 61 publications
17
146
2
Order By: Relevance
“…However, recent studies have revealed that noise correlations in visual areas also reflect slow internal fluctuations that are shared between groups of neurons and proposed that such fluctuations are the main source of experimentally measured noise correlations (12)(13)(14)(15)(16). However, the impact of this prominent source of correlation on information is largely unknown, except for two empirical studies of auditory (43) and visual (44) cortex whose results are based on small groups of neurons and cannot be extrapolated to large populations. Extrapolation from small populations to large populations is indeed prone to very large errors (7).…”
Section: Resultsmentioning
confidence: 99%
“…However, recent studies have revealed that noise correlations in visual areas also reflect slow internal fluctuations that are shared between groups of neurons and proposed that such fluctuations are the main source of experimentally measured noise correlations (12)(13)(14)(15)(16). However, the impact of this prominent source of correlation on information is largely unknown, except for two empirical studies of auditory (43) and visual (44) cortex whose results are based on small groups of neurons and cannot be extrapolated to large populations. Extrapolation from small populations to large populations is indeed prone to very large errors (7).…”
Section: Resultsmentioning
confidence: 99%
“…To identify sets of trials in each recording that were likely to have either strong or weak noise correlations, we measured the level of cortical synchronization. Previous studies have shown that noise correlations are strong when the cortex is in a synchronized state, where activity is dominated by concerted, large-scale fluctuations, and weak when the cortex is in a desynchronized state, where these fluctuations are suppressed (Pachitariu et al, 2015; Schölvinck et al, 2015). …”
Section: Resultsmentioning
confidence: 99%
“…These dynamics can create correlations in the activity of neuronal populations with important consequences for coding and computation (Shadlen et al, 1996; Abbott and Dayan, 1999; Averbeck et al, 2006). The correlations between pairs of neurons have been studied extensively (Cohen and Kohn, 2011; Ecker et al, 2010; Averbeck et al, 2006), and recent studies have demonstrated that they are driven by dynamics involving coordinated, large-scale fluctuations in the activity of many cortical neurons (Sakata and Harris, 2009; Pachitariu et al, 2015; Okun et al, 2015). Inactivation of the cortical circuit suppresses these synchronized fluctuations at the level of the membrane potential, in both awake and anesthetized animals, suggesting that this synchronization is cortical in origin (Cohen-Kashi Malina et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A substantial portion of correlations may also be explained by global fluctuations in which the firing of many neurons increases or decreases together on each trial (Ecker et al 2014, Goris et al 2014, Pachitariu et al 2015, Schölvinck et al 2015). The widespread cofluctuations of cortical activity were first observed using voltage-sensitive dye imaging of macaque V1, which revealed spatially extensive regions of coherent hyper- and depolarization (Arieli et al 1996).…”
Section: Sources Of Correlationsmentioning
confidence: 99%
“…Two recent studies have reported that information is affected by global fluctuations, based on simulating (Lin et al 2015) or analyzing (Arandia-Romero et al 2016, Pachitariu et al 2015, using Shannon information) small ensembles. However, in large populations, only differential correlations can make information saturate.…”
Section: Sources Of Correlationsmentioning
confidence: 99%